Latitudinal species diversity and density of cryptic crustacean (Brachyura and Anomura) in micro-habitat Autonomous Reef Monitoring Structures across Kepulauan Seribu, Indonesia - GESTEN HAZERI; DWI LISTYO RAHAYU; BEGINER SUBHAN; ANDRIANUS SEMBIRING; AJI WAHYU ANGGORO; AHMAD TAUFIK GHOZALI; HAWIS H MADDUPPA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hazeri G, Rahayu DL, Subhan B, Sembiring A, Anggoro AW, Ghozali AT, Madduppa HH. 2019. Latitudinal species diversity and density of cryptic crustacean (Brachyura and Anomura) in micro-habitat Autonomous Reef Monitoring Structures across Kepulauan Seribu, Indonesia. Biodiversitas 20: 1466-1474. Kepulauan Seribu is located in the north of Jakarta and has historically been affected by anthropogenic activities. Based on its anthropogenic pressure, the archipelago is divided latitudinally into three main parts; the southern part, is a collection of islands located closest to Jakarta Bay and characterized by poor water quality, large sediment and pollutant inputs from nearby rivers, the central and north part that possesses a better water quality. Brachyura and Anomura are dominant crustacean groups in the ocean, which inhabited areas from littoral zone to the deep sea. However, its diversity and abundance are relatively understudied especially in the area where anthropogenic pressure is severe like Kepulauan Seribu.  The ARMS (Autonomous Reef Monitoring Structure) is a standardized monitoring method systematically designed for observing indications of organism’s biodiversity in units of time. This research was conducted by employing ARMS as a standardize monitoring procedure to catalog and provide census of Crustaceans (Brachyuran and Anomuran) distributed across the archipelago. All crustacean inhabiting each unit of ARMS were collected and identified. Species diversity was then evaluated to see whether gradient in anthropogenic pressure has a direct impact on species composition and abundance. A total of 24 ARMS units were deployed from 2013 to 2016, located in three zones: south (9), central (9) and north (6) of Kepulauan Seribu. This study identified 17 species from 8 different families of Brachyura and 11 Anomura species from 4 different families from all sites. However, low available identification references for Indonesian crustacean made some specimen were identified only up to family level. The highest species diversity of Brachyura was recorded from family Xanthidae, followed by Portunidae and Pilumnidae, while in Anomura was in Porcellanidae, followed by Paguridae, Galatheidae, and Diogenidae. The high species diversity and density of brachyurans and anomurans were recorded in the central zone. This research infers that the species diversity of Crustaceans (Brachyura dan Anomura) seems dependent on the environmental quality, but most likely all crustacean species depend on the availability of habitat structure.